COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING MEETINGS IN PANGI VILLAGE BAOLAN DISTRICT TOLITOLI REGENCY: PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN PERTEMUAN PERENCANAAN DI DESA PANGI DISTRIK BAOLAN, KABUPATEN TOLITOLI - Samdy, Nur (STIE MUJAHIDIN TOLITOLI, 2024)
Development at the village level is a crucial aspect in the development of a country. Community participation in the development planning process has a very important role in determining the success of the development program. This research aims to identify the level of community participation in development planning deliberations, as well as the factors that influence their level of participation. The research method used is qualitative research with data collection through interviews, observation and documentation studies. The research results show that community participation in development planning deliberations in Pangi Village still faces a number of challenges, such as a lack of community awareness of the importance of their role in the process, as well as communication obstacles and information accessibility. However, there are also a number of factors that increase community participation, such as the active involvement of the village government and awareness of the benefits that can be obtained through participation in the development planning process.